Controllability Attribution as a Mediator in the Effect of Mindset on Achievement Goal Adoption Following Failure - Song, Juyeon; Kim, Sung-il; Bong, Mimi (Frontiers in Psychology, 2020)
The purpose of this study was to examine the effect of a growth mindset on achievement goal adoption in the face of failure. We also sought to investigate the mediating role of controllability attribution in order to understand the underlying process behind the effect of mindset on achievement goal adoption following failure. One hundred and seventy-two 4th and 5th grade students participated in an experimental task. In the manipulation phase, in related to the experimental task, 71 participants were provided with growth mindset-based information, and the other 101 were provided with fixed mindset-based information. After completing the experimental task on a computer, all participants were informed that they had failed the task. The participants then responded to controllability attribution and achievement goal scales. We empirically demonstrated that a growth mindset had a positive influence on mastery goal adoption, while it did not predict performance goal adoption. We also found that controllability attribution had a full mediation effect on the relationship between the presence of a growth mindset and mastery goal adoption; this finding implies that a key element in promoting the adoption of mastery goals following failure is attributing the failure to controllable causes, a belief which arises from a stronger growth mindset.